Magnetic Resonance Image Intensity Ratio, A Normalized Measure to Enable Inter-Patient Comparability of Left Atrial Fibrosis - Khurram, Irfan M. (2013)
BACKGROUND: The measurement of late gadolinium enhanced MRI (LGE-MRI) intensity in arbitrary units (au), limits the objectivity of thresholds for focal scar detection and inter-patient comparisons of scar burden. OBJECTIVE: We sought to develop and validate a normalized measure, the image intensity ratio (IIR), for assessment of left atrial (LA) scar on LGE-MRI. METHODS: ECG- and respiratory-gated 1.5 Tesla LGE-MRI was performed in 75 patients (75% male, 62±8 years) prior to atrial fibrillation (AF) ablation. The local IIR was defined as LA myocardial signal intensity for each of 20 sectors on contiguous axial image planes divided by the mean LA blood pool image intensity. Intra-cardiac point-by-point sampled electro-anatomical map (EAM) points were co-registered with corresponding image sectors. RESULTS: The average bipolar voltage for all 8,153 EAM points was 0.9±1.1 mV. In a mixed effects model accounting for within patient clustering, and adjusting for age, LA volume and mass, body mass index, gender, CHA(2)DS(2)-VASc score, AF type, history of previous ablations, and contrast delay time, each unit increase in local IIR was associated with 91.3% decrease in bipolar LA voltage (P<0.001). Local IIR thresholds of >0.97 and >1.61 corresponded to bipolar voltage <0.5 mV and <0.1 mV, respectively. CONCLUSION: Normalization of LGE-MRI intensity by the mean blood pool intensity results in a metric that is closely associated with intra-cardiac voltage as a surrogate of atrial fibrosis.